Endogenous activity rhythms and the reproductive response to photoperiod in the reddish grey musk shrew and eastern rock elephant shrew - Bennett, Nigel Charles (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2010.